TELEWORK IN EU: ASPECTS OF LEGAL REGULATION - Гаращенко, Людмила Петрівна; Гаращенко, Вадим Вікторович (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2018)
Objective: the article is devoted to the study of telework in the European Union and in some European countries, in particular Belgium, Italy, France and Poland. Methods of research: the legislation of the EU and some EU member-states on telework is analyzed. Hermeneutical and comparative research methods are mainly used. Results: it is concluded that the study of legal regulation of telework in the EU and EU member-states is positive in the context of improving labor legislation and the application of new forms and types of atypical employment in Ukraine. The experience of legal regulation of telework of foreign countries will help to find a mechanism for the application and settlement of new forms and types of atypical employment in Ukraine. Discussion: on the feasibility of legal regulation of telework in the labor legislation of Ukraine. The predominance of standard employment was characteristic only for a limited historical period and for a certain group of countries. The history of non-standard employment is much longer, and the geographical range of its distribution is much wider. Typical employment refers to the organization of a fixed-term employment contract in the form of a full-time employment contract in an enterprise or organization, under the direct supervision of the employer or authorized persons. By the mid-1970s the complex of conditions in which standard employment could dominate began to collapse. Structural changes in the economies of developed countries led to a reduction in the share of traditional large-scale industry, which was the main «consumer» of «standard» workers. The fast-growing sector of services needed other employees: working in a flexible temporary regime, and for a duration shorter or longer than required by law; more mobile and, if necessary, available for quick reallocation, and therefore those who have only a temporary employment contract, combine executive and business functions, etc. The demand for labor from small enterprises, whose role in the modern economy is constantly growing, is similar. Increasing global competition, as well as related uncertainty, increased competition for consumers and the need to reduce costs, demanded both from employers and from employees more flexibility in labor relations. The described labor market demands led to the establishment of a tendency to shift from permanent employment to temporary employment; from full employment - to incomplete. Non-standard forms of employment are becoming more widespread in the modern world. These forms of employment are temporary work, work under conditions of part-time work, distance work, labor, and others.